A single atom Ir doped heterophase of a NiMoP-NiMoPxOy ultrathin layer assembled on CNTs-graphene for high-performance water splitting. Issue 27 (30th June 2022) - Hoa, Van Hien; Prabhakaran, Sampath; Nhi Le, Kha Thuy; Kim, Do Hwan
Abstract : Rationally designed bifunctional electrocatalyst, Ir-NiMoP-NiMoP x O y /CNTs-Gr/Cu, required only 1.47 V at 10 mA cm −2 for overall water splitting with outstanding stability after 150 h. Abstract : The rational construction of efficient and robust with a high-performance electrocatalyst have been required in industrial green H2 production. In this study, single atom Iridium (Ir) introduced into both phases of an amorphous NiMoP x O y and crystalline NiMoP phase generates enriched active sites with high intrinsic activity, and the catalyst material coating on the carbon nanotube interconnected graphene sheet on copper foam (Ir-NiMoP-NiMoP x O y /CNTs-Gr/Cu) serves as an electron transport pathway and improves the surface area and protective layer. The engineered material exhibits excellent electrochemical water splitting characteristics, similar to those of Ir-NiMoP-MoNiP x O y /CNTs-Gr/Cu, showing a small overpotential of 138 mV for the hydrogen evolution reaction (HER) and 220 mV at 20 mA cm −2 for the oxygen evolution reaction (OER). The overall water splitting of Ir-NiMoP-NiMoP x O y /CNTs-Gr/Cu in 1.0 M KOH was extremely stable after 150 hours of operation at 50 mA cm −2 . Density functional theory calculations show that the real active sites are Ir and Mo in the hybrid amorphous/crystalline phase of Ir-NiMoP-MoNiP x O y, providing a new pathway for designing an effective catalyst for future applications in the hydrogen production field.